Nutrients extraction, growing and production of cucumber in hydroponic protected culture system - Ramírez-Vargas, Carlos (2019)
Three commercial genotypes of cucumber (Cucumis sativus L.), Modan RZ, Tropicuke y Monalisa, were grown in protected horticulture with open hydroponic system, in San Carlos, Costa Rica. Seedlings were transplant in pots ten liters capacity containing coconut fiber as substrate, irrigation system was installed, growing; production and nutrients contents were measured. Nutrients levels, growing and production were different between genotypes. Absorption order of macronutrients was K>N>Ca>Mg>P and micronutrients was Fe>Zn>Mn>Cu. Growing ranges of genotypes were 270.03 to 287.92 and 221.72 to 278.28 cm of maximum height, 61.86 to 82.83 and 18.27 a 20.75 leafs per plant, 432.98 to 562.83 and 148.88 to 202.47 cm2 in leaf area, 6.41 to 8.34 and 2.21 to 4.16 leaf area index, 294.86 to 349.70 and 174.94 to 206.50 g fresh weight vegetative, 342.60 to 361.97 and 203.67 to 274.40 g fresh weight of fruits, 21.38 to 27.76 and 13.55 to 15.38 g dry vegetative weight, 5.53 to 11.06 and 4.43 to 7.92 g dry weight of fruits. Yield was highest in the genotype Modan RZ with 2895.31 g/plant, and the smaller was 2001 g/plant.